The Cost of a Successful Delivery with in Vitro Fertilization - Peter J. Neumann; Soheyla Gharib; Milton C. Weinstein (1994)
The use of in vitro fertilization has engendered considerable debate about who should have the procedure, whether health insurance should cover the cost, and if so, to what extent. We investigated the cost of a successful delivery with in vitro fertilization.